Centering Single Cells in Microgels via Delayed Crosslinking Supports Long‐Term 3D Culture by Preventing Cell Escape. Issue 22 (28th April 2017) - Kamperman, Tom; Henke, Sieger; Visser, Claas Willem; Karperien, Marcel; Leijten, Jeroen
Abstract : Single‐cell‐laden microgels support physiological 3D culture conditions while enabling straightforward handling and high‐resolution readouts of individual cells. However, their widespread adoption for long‐term cultures is limited by cell escape. In this work, it is demonstrated that cell escape is predisposed to off‐center encapsulated cells. High‐speed microscopy reveals that cells are positioned at the microgel precursor droplets' oil/water interface within milliseconds after droplet formation. In conventional microencapsulation strategies, the droplets are typically gelled immediately after emulsification, which traps cells in this off‐center position. By delaying crosslinking, driving cells toward the centers of microgels is succeeded. The centering of cells in enzymatically crosslinked microgels prevents their escape during at least 28 d. It thereby uniquely enables the long‐term culture of individual cells within <5‐µm‐thick 3D uniform hydrogel coatings. Single cell analysis of mesenchymal stem cells in enzymatically crosslinked microgels reveals unprecedented high cell viability (>90%), maintained metabolic activity (>70%), and multilineage differentiation capacity (>60%) over a period of 28 d. The facile nature of this microfluidic cell‐centering method enables its straightforward integration into many microencapsulation strategies and significantly enhances control, reproducibility, and reliability of 3D single cell cultures. Abstract : Single‐cell‐laden microgels support physiological 3D culture conditions while enabling straightforward handling and high‐resolution readouts of individual cells. However, state‐of‐the‐art encapsulation strategies suffer from cell escape due to off‐center cell encapsulation. Here, the first microfluidic approach that enables long‐term 3D single cell culture by centering cells in microgels in a facile, modular, and widely applicable manner is presented.